2019
DOI: 10.1038/s41598-019-49614-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of consistent intra-individual locomotor patterns during zebrafish development

Abstract: The analysis of larval zebrafish locomotor behavior has emerged as a powerful indicator of perturbations in the nervous system and is used in many fields of research, including neuroscience, toxicology and drug discovery. The behavior of larval zebrafish however, is highly variable, resulting in the use of large numbers of animals and the inability to detect small effects. In this study, we analyzed whether individual locomotor behavior is stable over development and whether behavioral parameters correlate wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 93 publications
2
21
2
Order By: Relevance
“…Nonetheless, when the test groups are compared individually, the lidocaine-treated fish swim at 6H significantly slower than at 2H (Figure S1A), consistent with its sedative effect. In agreement with the studies showing high variability in locomotor behavior both in larvae (Fitzgerald et al, 2019) and in adults (Lange et al, 2013), we also noticed a high variability in the swimming speed between the individual fish across all groups, highlighting the complexity of behavioral studies.…”
Section: Resultssupporting
confidence: 92%
“…Nonetheless, when the test groups are compared individually, the lidocaine-treated fish swim at 6H significantly slower than at 2H (Figure S1A), consistent with its sedative effect. In agreement with the studies showing high variability in locomotor behavior both in larvae (Fitzgerald et al, 2019) and in adults (Lange et al, 2013), we also noticed a high variability in the swimming speed between the individual fish across all groups, highlighting the complexity of behavioral studies.…”
Section: Resultssupporting
confidence: 92%
“…Both authors concluded that activity was less variable when measured in the afternoon. In contrast to both studies, Fitzgerald et al [37] reported that time of day did not change the activity of 5, 6 and 7 dpf larvae in the dark period of LMR-L/D measured at 9 a.m and 2 p.m., and activity was more variable in the afternoon rather than in the morning. However, a different temperature (26 °C versus 28 °C of the other studies) was used as rearing temperature and the controversial finding may have been caused by differences in growth and developmental stage.…”
Section: Time Of the Day For Analysismentioning
confidence: 74%
“…At the individual level, we observed a decrease of larval motility at 120 hpf at all dose rates during the dark phase of the larval motility test. Previous studies suggested that locomotion is strongly increased during this phase, allowing the detection of fine effects on photokinesis driven by deep-brain photoreceptors 33,34 . In addition to this effect on larval locomotion, we found subtle but significant changes in embryonic and cardiac activities at 24 hpf and 48 hpf respectively.…”
Section: Discussionmentioning
confidence: 97%